Comparison of Neuroprotective Effect of Bevacizumab and Sildenafil following Induction of Stroke in a Mouse Model. (29th May 2016) - Novitzky, Ivan; Marianayagam, Neelan J.; Weiss, Shirel; Muhsinoglu, Orkun; Fridman, Moran; Leibovitch, Tamar Azrad; Goldenberg-Cohen, Nitza; Michowiz, Shalom
Abstract : To evaluate the effect of bevacizumab and sildenafil on stroke parameters in a mouse model, middle cerebral artery occlusion was induced in male C57Bl/6 mice using an intra-arterial filament method. The filament was removed after 60 minutes, and the mice were immediately given a single intraperitoneal injection of saline, bevacizumab, or sildenafil. An additional group of mice (n = 7 ) received bevacizumab 6 h after MCAO induction. The mice were euthanized 24 hours later and evaluated for infarct area and brain edema using triphenyltetrazolium chloride staining and ImageJ. In the saline-treated mice (n = 16 ), total stroke volume was 19.20 ± 6.38  mm 3, mean penumbra area was 4.5 ± 2.03  mm 3, and hemispheric asymmetry was 106.5%. Corresponding values in the bevacizumab group (n = 19 ) were 17.79 ± 5.80  mm 3, 7.3 ± 3.5  mm 3, and 108.6%; in the delayed (6 h) bevacizumab injected mice (n = 7 ) they were 9.80 ± 8.00  mm 3, 2.4 ± 2.0  mm 3, and 98.2%; and in the sildenafil group (n = 16 ) they were 18.42 ± 5.41  mm 3, 5.7 ± 2.02  mm 3, and 109.9%. The bevacizumab group had a significantly larger mean penumbra area when given immediately and smaller total stroke area in both groups than the saline- (p = 0.03 ) and sildenafil-treated (p = 0.003 ) groups. Only delayed bevacizumab group had reduced edema. Bevacizumab, injected immediately or delayed after injury, exerts a neuroprotective/salvage effect, whereas immediate treatment with sildenafil does not. Inflammation may play a role in the neuroprotective effect.